4-3(p+2)=2(p-4)

Simple and best practice solution for 4-3(p+2)=2(p-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3(p+2)=2(p-4) equation:



4-3(p+2)=2(p-4)
We move all terms to the left:
4-3(p+2)-(2(p-4))=0
We multiply parentheses
-3p-(2(p-4))-6+4=0
We calculate terms in parentheses: -(2(p-4)), so:
2(p-4)
We multiply parentheses
2p-8
Back to the equation:
-(2p-8)
We add all the numbers together, and all the variables
-3p-(2p-8)-2=0
We get rid of parentheses
-3p-2p+8-2=0
We add all the numbers together, and all the variables
-5p+6=0
We move all terms containing p to the left, all other terms to the right
-5p=-6
p=-6/-5
p=1+1/5

See similar equations:

| 5x+3x=5-2 | | x+88=121 | | k.12=-5k-3 | | -8x+2=28 | | (6x+1)/(2x-1)=9 | | 0.5(5-7x=8-1(4x+6) | | 4+3(w-9)=-12 | | P(x)=-6x-9 | | 5x+3x=2+5 | | 7x−9=4x | | 43+8p=p+21 | | 2x+45=87 | | 13+2a=3a-14+24 | | 14v+50=2(5v+29) | | 420(2r+10=) | | -w+66=2w | | 8x=x2+15 | | n4+5=17 | | y2-144=0 | | 4-3t=6t-8 | | 3x-9-3=2x+14 | | Y=6E-06x | | 18c–25=38 | | 4(n+5)=17 | | -5(x+2)+16=15-6x | | −5(x+2)+16=15−6x | | 2d−6=2 | | 3x+(4x+13)=125 | | 0.4(2x+1/2)=3(0.2+(-2))-4 | | 3x-10=2x+14 | | 15y+18=-6y+10 | | x+2x+2x+3=31 |

Equations solver categories